Optimisation of imaging protocols in interventional cardiology: impact on patient doses. (28th July 2017) - Ordiales, J M; Vano, E; Nogales, J M; Ramos, J; López-Mínguez, J R; Martínez, G; Cerrato, P; Álvarez, F J
Abstract: The purpose of this work is to evaluate the impact of the imaging protocol as part of the optimisation of patient doses in interventional cardiology. This paper reports the results of an initial study to refine the existing fluoroscopy and cine settings, evaluates a new imaging protocol by measuring the image quality and phantom entrance air kerma values, and tests the clinical implementation of the new protocol in terms of the reduction in patient doses and the impact on clinical images. The initial study developed a new fluoroscopy mode using 7.5 frames s −1 (instead of the previous 15 frames s −1 ) with a similar dose/frame and a reduction of approximately 26% in dose/frame for the existing standard cine mode. For the new imaging protocol, the reduction in entrance air kerma was characterised for water depths of 16, 20, and 24 cm and the image quality was evaluated using a Leeds test object. A reduction in dose of around 50% was observed for the low fluoroscopy mode and an 18%–38% reduction was measured for cine. The image quality was unchanged in fluoroscopy mode and did not suffer noticeable alterations in cine mode. In the clinical implementation, cardiologists evaluated the new imaging protocol in clinical practice and cooperated with medical physicists to ensure full optimisation. The image quality criteria evaluated the ability to visualise the standard coronary arteries and small vessels (<2 mm), and the proper visualisation of the heart and diaphragm. A total of 1635 interventional cardiac procedures were assessed. The median kerma-area product exhibited a reduction of 37% for CA and 43% for PTCA examinations, and the quality of the clinical images was considered sufficient for standard clinical practice.